When loss is gain - "Varma, Pavan K." (New Delhi, 2012)
Diagnosed with pancreatic cancer and given only a few months to live. Anand. a budding Delhi lawyer, who is obsessed with his own ambition and the politics of his workplace. thinks his life has hit rock bottom. But then further misfortune strikes: his wife Taint leaves him for his best friend Mi. the owner of the law firm for which he works. As Anand surveys the wreckage of everything that has mattered to him, and realizes how misplaced his priorities have been, he is unexpectedly granted a reprieve.
Keywords: Fiction